Third-Party Binding of Prenuptial Deeds After Decision 69/PUU-XIII/2015 - Ade Furota Husna; Abdul Rachmad Budiono; KRA MJ Widijatmoko (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
This study examines the legal meaning of the phrase